Autonomía y educación - Martínez Herrera, Abel (2023)
In this article I explore the concept of autonomy as a permanent reflection exercise that helps develop a critical and philosophical attitude, which enables in education to reach “adulthood”, in the sense proposed by Kant. From the kantian perspective autonomy is understood as the ability of the individual to own one’s own thought, ie to give up a passive mentality does not impose any view of the reason the contradictions, appearance, traditions and customs, which generate dependence and blind faith in any kind of authority that is created with the right to be elected as judge and ruler of the world. It can also be said in line with Kant’s thought that autonomy constitutes a categorical imperative that put myself in someone else’s place, not to reject their views, but on the contrary make them useful for our own lives. Similarly to reach the majority age we must persevere in being, that has telos as the coherence and consistency in thought.